The Influence of Price, Product Quality, Brand Image, Religiosity, and Social Media Marketing on The Purchase Decision of Halal Cosmetic Products on The Shopee Marketplace - Raden Hendri Gusaptono; Saskhia Rheicha Faraz (Kaunia: Integration and Interconnection Islam and Science Journal, 2026)
Introduction: In recent years, marketplaces in Indonesia have experienced rapid development and become one of the most dynamic sectors of the digital economy. Indonesian consumers are increasingly accustomed to the convenience of online shopping . They seek convenience in shopping, the ability to compare prices, and the ease of finding a wider variety of products. Marketplace platforms offer this flexibility, allowing consumers to purchase goods from various categories quickly and easily. This has led to a significant increase in online purchases for everyday needs. Methods: This quantitative investigation utilized primary data collected via a questionnaire survey administered to 152 participants. The sampling method was purposive sampling. Subsequent to collection, the data underwent processing and analysis utilizing the SPSS statistical software. Results: The findings indicate that price, product quality, brand image, religiosity and social media marketing significantly influence purchasing decisions. In addition, purchasing decisions also underline the importance of aligning these purchasing decision factors with consumer needs. Conclusion and suggestion: This research examines the factors impacting consumer purchasing decisions of halal cosmetics within the Shopee e-commerce platform. The findings indicate that price, product quality, brand image, religiosity and social media marketing significantly influence purchasing decisions. Most studies rely on quantitative methodologies, such as surveys and structural equation modeling, which may limit the depth of understanding of the motivations and experiences underlying students’ halal cosmetic purchasing decisions. This limitation opens up opportunities for further research that can examine the relationship between these findings and different contexts or methodologies.